Cholesterol modulates the structure, binding modes, and energetics of caveolin-membrane interactions - Sengupta, Durba (Journal of Physical Chemistry B, 2012)
Caveolin-1 (cav-1) is an important membrane protein that plays a vital role in cellular signaling and trafficking by organizing membrane domains. The peptide interacts with cholesterol-rich membranes and induces large morphological changes in them, forming microdomains such as caveolae. Here, we use coarse-grain molecular dynamics simulations to study the interaction of cav-1 peptides with several model bilayer systems mimicking biological scenarios, such as cholesterol-rich domains, cholesterol-depleted domains, and unsaturated lipid domains. We show that cholesterol modulates the depth as well as orientation of cav-1 binding to membranes. Furthermore, the presence of cholesterol stabilizes more open conformations of cav-1, and we speculate that the binding modes and open conformations could be responsible for inducing morphological changes in the bilayer. We also calculated the partitioning free energy to different bilayers and show that binding to cholesterol-rich bilayers is more favorable than cholesterol-depleted bilayers and the binding to unsaturated bilayers is the least favorable. Binding to cholesterol-rich bilayers also changes the pressure profile of the bilayer to which it is bound and thereby affects the local spontaneous curvature. Our results highlight molecular details of protein-lipid interplay and provide new insights into the effects of cav-1 in tuning the morphology of cholesterol-rich membranes.

Identification of cholesterol binding sites in the serotonin(1A) receptor - Sengupta, Durba; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2012)
The serotonin(1A) receptor is a representative member of the G protein-coupled receptor (GPCR) superfamily and serves as an important drug target in the development of therapeutic agents for neuropsychiatric disorders. Previous work has shown the requirement of membrane cholesterol in the organization, dynamics, and function of the serotonin(1A) receptor. We show here that membrane cholesterol binds preferentially to certain sites on the serotonin(1A) receptor by performing multiple, long time scale MARTINI coarse-grain molecular dynamics simulations. Interestingly, our results identify the highly conserved cholesterol recognition/interaction amino acid consensus (CRAC) motif on transmembrane helix V as one of the sites with high cholesterol occupancy, thereby confirming its role as a putative cholesterol binding motif. These results represent the first direct evidence for membrane cholesterol binding to specific sites on the serotonin(1A) receptor and represent an important step in our overall understanding of GPCR function in health and disease.

Multi-Hit action of membrane active peptides: towards understanding bacterial cell killing - Moiset, Gemma; Cirac, Anna D.; Mika, Jacek T.; Kocer, Armagan; Stuart, Marc C. A.; Sengupta, Durba; Marrink, Siewert-Jan; Poolman, Bert (Biophysical Journal, 2012)

Dual action of BPC194: a membrane active peptide killing bacterial cells - Moiset, Gemma; Cirac, Anna D.; Stuart, Marc C. A.; Marrink, Siewert-Jan; Sengupta, Durba; Poolman, Bert (Plos One, 2013)
Membrane active peptides can perturb the lipid bilayer in several ways, such as poration and fusion of the target cell membrane, and thereby efficiently kill bacterial cells. We probe here the mechanistic basis of membrane poration and fusion caused by membrane-active, antimicrobial peptides. We show that the cyclic antimicrobial peptide, BPC194, inhibits growth of Gram-negative bacteria and ruptures the outer and inner membrane at the onset of killing, suggesting that not just poration is taking place at the cell envelope. To simplify the system and to better understand the mechanism of action, we performed Forster resonance energy transfer and cryogenic transmission electron microscopy studies in model membranes and show that the BPC194 causes fusion of vesicles. The fusogenic action is accompanied by leakage as probed by dual-color fluorescence burst analysis at a single liposome level. Atomistic molecular dynamics simulations reveal how the peptides are able to simultaneously perturb the membrane towards porated and fused states. We show that the cyclic antimicrobial peptides trigger both fusion and pore formation and that such large membrane perturbations have a similar mechanistic basis.

Sequence dependent lipid-mediated effects modulate the dimerization of ErbB2 and its associative mutants - Prasanna, Xavier; Praveen, P. J.; Sengupta, Durba (Physical Chemistry Chemical Physics, 2013)
The association of transmembrane helices is an important event in several biological processes, but the factors governing association, especially the non-specific environmental effects, have still not been elucidated. Here, we use coarse-grain molecular dynamics simulations to study the association of ErbB2 transmembrane helices and three ``oncogenic mutants.'' Self-assembly simulations and the dimerization free-energy profiles confirm an energetically-favorable dimerized state for both the wildtype and the mutants. The dissociation free energy of all three mutants is calculated to be larger than the wildtype peptide. Along with favourable protein-protein interactions, non-specific environmental effects are observed to contribute to the association. In particular, local bilayer thinning along with membrane perturbations are seen around the mutants. The membrane perturbations are reduced upon helix association, suggesting that lipid chain packing is an important driving force for helix dimerization. Our results highlight the importance of both specific as well as non-specific driving forces in the association of transmembrane helices.

Cholesterol modulates the dimer interface of the beta(2)-adrenergic receptor via cholesterol occupancy sites - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2014)
The beta(2)-adrenergic receptor is an important member of the G-protein-coupled receptor (GPCR) superfamily, whose stability and function are modulated by membrane cholesterol. The recent high-resolution crystal structure of the beta(2)-adrenergic receptor revealed the presence of possible cholesterol-binding sites in the receptor. However, the functional relevance of cholesterol binding to the receptor remains unexplored. We used MARTINI coarse-grained molecular-dynamics simulations to explore dimerization of the beta(2)-adrenergic receptor in lipid bilayers containing cholesterol. A novel (to our knowledge) aspect of our results is that receptor dimerization is modulated by membrane cholesterol. We show that cholesterol binds to transmembrane helix IV, and cholesterol occupancy at this site restricts its involvement at the dimer interface. With increasing cholesterol concentration, an increased presence of transmembrane helices I and II, but a reduced presence of transmembrane helix IV, is observed at the dimer interface. To our knowledge, this study is one of the first to explore the correlation between cholesterol occupancy and GPCR organization. Our results indicate that dimer plasticity is relevant not just as an organizational principle but also as a subtle regulatory principle for GPCR function. We believe these results constitute an important step toward designing better drugs for GPCR dimer targets.

Molecular Insights into the dynamics of pharmacogenetically important N-terminal variants of the human beta(2)-adrenergic receptor - Shahane, Ganesh; Parsania, Chirag; Sengupta, Durba; Joshi, Manali (Plos Computational Biology, 2014)
The human beta(2)-adrenergic receptor (beta(2)AR), a member of the G-protein coupled receptor (GPCR) family, is expressed in bronchial smooth muscle cells. Upon activation by agonists, beta(2)AR causes bronchodilation and relief in asthma patients. The N-terminal polymorphism of beta(2)AR at the 16th position, Arg16Gly, has warranted a lot of attention since it is linked to variations in response to albuterol (agonist) treatment. Although the beta(2)AR is one of the well-studied GPCRs, the N-terminus which harbors this mutation, is absent in all available experimental structures. The goal of this work was to study the molecular level differences between the N-terminal variants using structural modeling and atomistic molecular dynamics simulations. Our simulations reveal that the N-terminal region of the Arg variant shows greater dynamics than the Gly variant, leading to differential placement. Further, the position and dynamics of the N-terminal region, further, affects the ligand binding-site accessibility. Interestingly, long-range effects are also seen at the ligand binding site, which is marginally larger in the Gly as compared to the Arg variant resulting in the preferential docking of albuterol to the Gly variant. This study thus reveals key differences between the variants providing a molecular framework towards understanding the variable drug response in asthma patients.

Permeation of lipidated protein in bilayer using unbiased simulations reveals signature motif for protein-membrane binding - Thukral, Lipi; Sengupta, Durba; Gokhale, Rajesh S. (Biophysical Journal, 2014)

Differential dynamics of the serotonin(1A) receptor in membrane bilayers of varying cholesterol content revealed by all atom molecular dynamics simulation - Patra, Swarna M.; Chakraborty, Sudip; Shahane, Ganesh; Prasanna, Xavier; Sengupta, Durba; Maiti, Prabal K.; Chattopadhyay, Amitabha (Molecular Membrane Biology, 2015)
The serotonin(1A) receptor belongs to the superfamily of G protein-coupled receptors (GPCRs) and is a potential drug target in neuropsychiatric disorders. The receptor has been shown to require membrane cholesterol for its organization, dynamics and function. Although recent work suggests a close interaction of cholesterol with the receptor, the structural integrity of the serotonin(1A) receptor in the presence of cholesterol has not been explored. In this work, we have carried out all atom molecular dynamics simulations, totaling to 3s, to analyze the effect of cholesterol on the structure and dynamics of the serotonin(1A) receptor. Our results show that the presence of physiologically relevant concentration of membrane cholesterol alters conformational dynamics of the serotonin(1A) receptor and, on an average lowers conformational fluctuations. Our results show that, in general, transmembrane helix VII is most affected by the absence of membrane cholesterol. These results are in overall agreement with experimental data showing enhancement of GPCR stability in the presence of membrane cholesterol. Our results constitute a molecular level understanding of GPCR-cholesterol interaction, and represent an important step in our overall understanding of GPCR function in health and disease.
Keywords: GPCR; Membrane cholesterol; molecular dynamics simulation; serotonin(1A) receptor

Effect of lipid bilayer composition on membrane protein association - Pawar, Aiswarya B.; Prasanna, Xavier; Sengupta, Durba (Advances in Planar Lipid Bilayers and Liposomes, 2015)
Diverse cellular functions are supported by membrane protein assemblies associated with the cell membrane. Although considered to be protein-mediated, membrane components are now being recognized as critical in modulating and sometime dictating function. This chapter discusses the effect of the lipid bilayer, in particular its composition on membrane protein organization. Computational methods have been successful in quantifying transmembrane protein association and general features of dimerization profiles are explored. Understanding the molecular basis of the interactions has lead to the recognition of the lipophobic effects. These nonspecific effects include those that arise from membrane perturbations and lipid chain packing and have been shown to modulate the energetics as well as the structural characteristics of membrane protein dimerization. In addition, specific interactions arising from direct protein–lipid interactions and protein–cholesterol interactions have been suggested to influence membrane protein association. We summarize here a few examples highlighting the role of the lipid bilayer on membrane protein organization.

High-throughput simulations of dimer and trimer assembly of membrane proteins. the DAFT approach - Wassenaar, Tsjerk A.; Pluhackova, Kristyna; Moussatova, Anastassiia; Sengupta, Durba; Marrink, Siewert-Jan; Tieleman, D. Peter; Boeckmann, Rainer A. (Journal of Chemical Theory and Computation, 2015)
Interactions between membrane proteins are of great biological significance and are consequently an important target for pharmacological intervention. Unfortunately, it is still difficult to obtain detailed views on such interactions, both experimentally, where the environment hampers atomic resolution investigation, and computationally, where the time and length scales are problematic. Coarse grain simulations have alleviated the later issue, but the slow movement through the bilayer, coupled to the long life times of nonoptimal dimers, still stands in the way of characterizing binding distributions. In this work, we present DAFT, a Docking Assay For Transmembrane components, developed to identify preferred binding orientations. The method builds on a program developed recently for generating custom membranes, called insane (INSert membrANE). The key feature of DAFT is the setup of starting structures, for which optimal periodic boundary conditions are devised. The purpose of DAFT is to perform a large number of simulations with different components, starting from unbiased noninteracting initial states, such that the simulations evolve collectively, in a manner reflecting the underlying energy landscape of interaction. The implementation and characteristic features of DAFT are explained, and the efficacy and relaxation properties of the method are explored for oligomerization of glycophorin A dimers, polyleucine dimers and trimers, MS1 trimers, and rhodopsin dimers. The results suggest that, for simple helices, such as GpA and polyleucine, in POPC/DOPC membranes series of 500 simulations of 500 ns each allow characterization of the helix dimer orientations and allow comparing associating and nonassociating components. However, the results also demonstrate that short simulations may suffer significantly from nonconvergence of the ensemble and that using too few simulations may obscure or distort features of the interaction distribution. For trimers, simulation times exceeding several microseconds appear needed, due to the increased complexity. Similarly, characterization of larger proteins, such as rhodopsin, takes longer time scales due to the slower diffusion and the increased complexity of binding interfaces. DAFT and its auxiliary programs have been made available from http://cgmartini.nl/, together with a working example.

Landscapes of membrane protein interactions from high-throughput MD simulations using the daft approach - Wassenaar, Tsjerk A.; Pluhackova, Kristyna; Moussatova, Anastassiia; Sengupta, Durba; Marrink, Siewert-Jan; Tieleman, D. Peter; Boeckmann, Rainer A. (Biophysical Journal, 2015)

Molecular dynamics simulations of GPCR-cholesterol interaction: an emerging paradigm - Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica Et Biophysica Acta-Biomembranes, 2015)
G protein-coupled receptors (GPCRs) are the largest class of molecules involved in signal transduction across cell membranes and represent major targets in the development of novel drug candidates. Membrane cholesterol plays an important role in GPCR structure and function. Molecular dynamics simulations have been successful in exploring the effect of cholesterol on the receptor and a general consensus molecular view is emerging. We review here recent molecular dynamics studies at multiple resolutions highlighting the main features of cholesterol-GPCR interaction. Several cholesterol interaction sites have been identified on the receptor that are reminiscent of nonannular sites. These cholesterol hot-spots are highly dynamic and have a microsecond time scale of exchange with the bulk lipids. A few consensus sites (such as the CRAC site) have been identified that correspond to higher cholesterol interaction. Interestingly, high plasticity is observed in the modes of cholesterol interaction and several sites have been suggested to have high cholesterol occupancy. We therefore believe that these cholesterol hot-spots are indicative of `high occupancy sites' rather than `binding sites'. The results suggest that the energy landscape of cholesterol association with GPCRs corresponds to a series of shallow minima interconnected by low barriers. These specific interactions, along with general membrane effects, have been observed to modulate GPCR organization. Membrane cholesterol effects on receptor structure and organization, that in turn influences receptor cross-talk and drug efficacy, represent a new frontier in GPCR research. This article is part of a Special Issue entitled: Lipid-protein interactions. Guest Editors: Amitabha Chattopadhyay and jean-Marie Ruysschaert. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Coarse-grain simulation; CRAC; GPCR; Lipid-receptor interaction; Membrane cholesterol; Receptor dimerization

Molecular mechanism underlying recruitment and insertion of lipid-anchored LC3 protein into membranes - Thukral, Lipi; Sengupta, Durba; Ramkumar, Amrita; Murthy, Divya; Agrawal, Nikhil; Gokhale, Rajesh S. (Biophysical Journal, 2015)
Lipid modification of cytoplasmic proteins initiates membrane engagement that triggers diverse cellular processes. Despite the abundance of lipidated proteins in the human proteome, the key determinants underlying membrane recognition and insertion are poorly understood. Here, we define the course of spontaneous membrane insertion of LC3 protein modified with phosphatidylethanolamine using multiple coarse-grain simulations. The partitioning of the lipid anchor chains proceeds through a concerted process, with its two acyl chains inserting one after the other. Concurrently, a conformational rearrangement involving the alpha-helix III of LC3, especially in the three basic residues Lys(65), Arg(68), and Arg(69), ensures stable insertion of the phosphatidylethanolamine anchor into membranes. Mutational studies validate the crucial role of these residues, and further live-cell imaging analysis shows a substantial reduction in the formation of autophagic vesicles for the mutant proteins. Our study captures the process of water-favored LC3 protein recruitment to the membrane and thus opens, to our knowledge, new avenues to explore the cellular dynamics underlying vesicular trafficking.

Role of lipid-mediated effects in beta(2)-adrenergic receptor dimerization - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (biochemical roles of eukaryotic cell surface macromolecules, 2015)

Thermodynamic and kinetic characterization of transmembrane helix association - Pawar, Aiswarya B.; Deshpande, Sneha A.; Gopal, Srinivasa M.; Wassenaar, Tsjerk A.; Athale, Chaitanya A.; Sengupta, Durba (Physical Chemistry Chemical Physics, 2015)
The transient dimerization of transmembrane proteins is an important event in several cellular processes and computational methods are being increasingly used to quantify their underlying energetics. Here, we probe the thermodynamics and kinetics of a simple transmembrane dimer to understand membrane protein association. A multi-step framework has been developed in which the dimerization profiles are calculated from coarse-grain molecular dynamics simulations, followed by meso-scale simulations using parameters calculated from the coarse-grain model. The calculated value of Delta G(assoc) is approx. -20 kJ mol(-1) and is consistent between three methods. Interestingly, the meso-scale stochastic model reveals low dimer percentages at physiologically-relevant concentrations, despite a favorable Delta G(assoc). We identify generic driving forces arising from the protein backbone and lipid bilayer and complementary factors, such as protein density, that govern self-interactions in membranes. Our results provide an important contribution in understanding membrane protein organization and linking molecular, nano-scale computational studies to meso-scale experimental data.

Cholesterol-dependent conformational plasticity in GPCR dimers - Prasanna, Xavier; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
The organization and function of the serotonin1A receptor, an important member of the GPCR family, have been shown to be cholesterol-dependent, although the molecular mechanism is not clear. We performed a comprehensive structural and dynamic analysis of dimerization of the serotonin1A receptor by coarse-grain molecular dynamics simulations totaling 3.6 ms to explore the molecular details of its cholesterol-dependent association. A major finding is that the plasticity and flexibility of the receptor dimers increase with increased cholesterol concentration. In particular, a dimer interface formed by transmembrane helices I-I was found to be sensitive to cholesterol. The modulation of dimer interface appears to arise from a combination of direct cholesterol occupancy and indirect membrane effects. Interestingly, the presence of cholesterol at the dimer interface is correlated with increased dimer plasticity and flexibility. These results represent an important step in characterizing the molecular interactions in GPCR organization with potential relevance to therapeutic interventions.

Conformational dynamics of GPCR dimers is dependent on membrane cholesterol - Sengupta, Durba; Prasanna, Xavier; Chattopadhyay, Amitabha (Biophysical Journal, 2016)

Ganglioside GM1 interacts with the serotonin1A receptor via the sphingolipid binding domain - Prasanna, X.; Jafurulla, M.; Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica et Biophysica Acta, 2016)
Glycosphingolipids are minor yet essential components of eukaryotic cell membranes and are involved in a variety of cellular processes. Although glycosphingolipids such as GM1 have been previously reported to influence the function of G protein-coupled receptors (GPCRs), the molecular mechanism remains elusive. In this paper, we have explored the interaction of GM1 with the serotonin1A receptor, an important neurotransmitter receptor that belongs to the GPCR family. To examine the molecular basis of the interaction of GM1 with the serotonin1A receptor, we performed a series of coarse-grain molecular dynamics simulations of the receptor embedded in membrane bilayers containing GM1. Our results show that GM1 interacts with the serotonin1A receptor predominantly at the extracellular loop 1 and specifically at the sphingolipid binding domain (SBD). The SBD motif consists of a characteristic combination of aromatic, basic and turn-inducing residues, and is evolutionarily conserved in case of the serotonin1A receptor. The interaction of the SBD site with GM1 appears to stabilize a 'flip-out' conformation in which W102 of the extracellular loop 1 flips out from the central lumen of the receptor toward the membrane. The population of the 'flip-out' conformation is increased in the presence of cholesterol. Our data strongly suggest that a direct interaction between GM1 and the SBD site of the serotonin1A receptor may occur in vivo. In view of the reported role of GM1 and the serotonin1A receptor in neurodegenerative diseases, GM1-receptor interaction assumes significance in the context of malfunctioning of neuronal GPCRs under such conditions.

Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

Structural insights and functional implications of inter-individual variability in beta(2)-adrenergic receptor - Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Scientific Reports, 2016)
The human beta(2)-adrenergic receptor (beta(2)AR) belongs to the G protein-coupled receptor (GPCR) family and due to its central role in bronchodilation, is an important drug target. The inter-individual variability in beta(2)AR has been implicated in disease susceptibility and differential drug response. In this work, we identified nine potentially deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) using a consensus approach. The deleterious nsSNPs were found to cluster near the ligand binding site and towards the G-protein binding site. To assess their molecular level effects, we built structural models of these receptors and performed atomistic molecular dynamics simulations. Most notably, in the Phe290Ser variant we observed the rotameric flip of Trp286(6.48), a putative activation switch that has not been reported in beta(2)AR thus far. In contrast, the variant Met82Lys was found to be the most detrimental to epinephrine binding. Additionally, a few of the nsSNPs were seen to cause perturbations to the lipid bilayer, while a few lead to differences at the G-protein coupling site. We are thus able to classify the variants as ranging from activating to damaging, prioritising them for experimental studies.

Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

What can simulations tell us about GPCRs: integrating the scales - Sengupta, Durba; Joshi, Manali; Athale, Chaitanya A.; Chattopadhyay, Amitabha (G Protein-Coupled Receptors: Signaling, Trafficking and Regulation, 2016)
The functional dynamics of G protein-coupled receptors (GPCRs) encompasses multiple spatiotemporal scales, ranging from femtoseconds to seconds and Angstroms to micrometers. Computational approaches, often in close collaboration with experimental methods, have been invaluable in unraveling GPCR structure and dynamics at these various hierarchical levels. The binding of natural and synthetic ligands to the wild-type and naturally occurring variant receptors have been analyzed by several computational methods. The activation of receptors from the inactive to the active state has been investigated by atomistic simulations and ongoing work on several receptors will help uncover general and receptor-specific mechanisms. The interaction of GPCRs with complex membranes that contain phospholipids and cholesterol have been probed by coarse-grain methods and shown to directly influence receptor association. In this chapter, we discuss computational approaches that have been successful in analyzing each scale of GPCR dynamics. An overview of these approaches will allow a more judicious choice of the appropriate method. We hope that an appreciation of the power of current computational approaches will encourage more critical collaborations. A comprehensive integration of the different approaches over the entire spatiotemporal scales promises to unravel new facets of GPCR function.

Chapter 5: Experimental and computational approaches to study membranes and lipid-protein interactions - Sengupta, Durba; Kumar, G. Aditya; Prasanna, Xavier; Chattopadhyay, A. (Computational biophysics of membrane proteins, 2017)
Biological membranes are complex two-dimensional, non-covalent assemblies of a diverse variety of lipids and proteins. A hallmark of membrane organization is varying degrees of spatiotemporal heterogeneity spanning a wide range. Membrane proteins are implicated in a wide variety of cellular functions, and comprise ∼30% of the human proteome and ∼50% of the current drug targets. Their interactions with membrane lipids are recognized as crucial elements in their function. In this article, we provide an overview of experimental and theoretical approaches to analyze membrane organization, dynamics, and lipid-protein interactions. In this context, we highlight the wide range of time scales that membrane events span, and approaches that are suitable for a given time scale. We discuss representative fluorescence-based approaches (FRET and FRAP) that help to address questions on lipid-protein and protein-cytoskeleton interactions in membranes. In a complimentary fashion, we discuss computational methods, atomistic and coarse-grain, that are required to address a given membrane problem at an appropriate scale. We believe that the synthesis of knowledge gained from experimental and computational approaches will enable us to probe membrane organization, dynamics, and interactions at increasing spatiotemporal resolution, thereby providing a robust model for the membrane in health and disease.

Characterizing clinically relevant natural variants of GPCRs using computational approaches - Sengupta, Durba; Sonar, Krushna; Joshi, Manali (Methods in cell biology, 2017)
G protein-coupled receptors (GPCRs) are an important class of drug targets owing to their physiological role. A large number of clinically relevant single nucleotide polymorphisms (SNPs) have been observed in GPCRs that are linked to disease susceptibility and adverse drug response. It is therefore important to characterize the variants in order to improve GPCR therapeutics. Here, we discuss computational methods coupling molecular dynamics simulations with docking and free energy calculations to characterize the functional differences in GPCR variants. The hallmark of this approach is the explicit incorporation of receptor and membrane dynamics that allows us to analyze short- and long-range effects in the variant receptors. We use the SNPs reported in β2-adrenergic receptor (β2AR) as a test case and highlight the recent successes in analyzing structural and dynamic differences in a series of population variants. The computational approach we discuss here has a twofold benefit: it helps to unravel the molecular mechanisms underlying hypo- or hyperfunctionality of variant receptors as well as prioritizing novel variants that must be experimentally tested.

Estimating the lipophobic contributions in model membranes - Dubey, Vikas; Prasanna, Xavier; Sengupta, Durba (Journal of Physical Chemistry B, 2017)
The insertion and association of membrane proteins is critical in several cellular processes. These processes were thought to be protein-driven, but increasing evidence points toward an important role of the lipid bilayer. The lipid-mediated contribution has been shown to be important in the association of membrane peptides, but the corresponding ``lipophobic'' component has not been directly estimated. Here, we calculate the free energy of insertion for transmembrane peptides and estimate the lipophobic component from the cost of cavity formation. The free-energy calculations were performed using the coarse-grain Martini force field, which has been successful in predicting membrane protein interactions. As expected, the charged moieties have the least favorable free energy of insertion and the highest cost of cavity formation. A length dependence was observed in polyalanine peptides with the lipid-mediated component increasing nonlinearly with peptide length. Membrane fluidity was tested by varying the temperature, and opposing effects were observed for short and long peptides. The dependence of the lipid-mediated effects on peptide length and temperature was not uniform and gives valuable insight into the anisotropic nature of the membrane. The results are an important step in estimating membrane effects in protein insertion and association.

Role of spatial inhomogenity in GPCR dimerisation predicted by receptor association-diffusion models - Deshpande, Sneha A.; Pawar, Aiswarya B.; Dighe, Anish; Athale, Chaitanya A.; Sengupta, Durba (Physical Biology, 2017)
G protein-coupled receptor (GPCR) association is an emerging paradigm with far reaching implications in the regulation of signalling pathways and therapeutic interventions. Recent super resolution microscopy studies have revealed that receptor dimer steady state exhibits sub-second dynamics. In particular the GPCRs, muscarinic acetylcholine receptor M-1 (M1MR) and formyl peptide receptor (FPR), have been demonstrated to exhibit a fast association/dissociation kinetics, independent of ligand binding. In this work, we have developed a spatial kinetic Monte Carlo model to investigate receptor homo-dimerisation at a single receptor resolution. Experimentally measured association/dissociation kinetic parameters and diffusion coefficients were used as inputs to the model. To test the effect of membrane spatial heterogeneity on the simulated steady state, simulations were compared to experimental statistics of dimerisation. In the simplest case the receptors are assumed to be diffusing in a spatially homogeneous environment, while spatial heterogeneity is modelled to result from crowding, membrane micro-domains and cytoskeletal compartmentalisation or 'corrals'. We show that a simple association-diffusion model is sufficient to reproduce M1MR association statistics, but fails to reproduce FPR statistics despite comparable kinetic constants. A parameter sensitivity analysis is required to reproduce the association statistics of FPR. The model reveals the complex interplay between cytoskeletal components and their influence on receptor association kinetics within the features of the membrane landscape. These results constitute an important step towards understanding the factors modulating GPCR organisation.

Dynamics of loops at the substrate entry channel determine the specificity of iridoid synthases - Sandholu, Anand S.; Mohole, Madhura; Duax, William L.; Thulasiram, Hirekodathakallu V.; Sengupta, Durba; Kulkarni, Kiran (Febs Letters, 2018)
Iridoid synthases belong to the family of short-chain dehydrogenase reductase involved in the biosynthesis of iridoids. Despite having high sequence and structural homology with progesterone 5 beta- reductase, these enzymes exhibit differential substrate specificities. Previously, two loops. L1 and L2 at substrate-binding pocket, were suggested to be involved in generating substrate specificity. However, the structural basis of specificity determinants was elusive. Here, combining sequence and structural analysis, site-directed mutagenesis, and molecular dynamics simulations, we have shown that iridoid synthase contains two channels for substrate entry whose geometries are altered by L1-L2 dynamics, primarily orchestrated by interactions of residues Glu161 and Gly162 of L1 and Asn358 of L2. A complex interplay of these interactions confer the substrate specificity to the enzyme.
Keywords: iridoid synthase; iridoids; Molecular dynamics simulations; progesterone 5 beta-reductase; Substrate specificity

Effect of membrane composition on receptor association: implications of cancer lipidomics on ErbB receptors - Pawar, Aiswarya; Sengupta, Durba (Journal of Membrane Biology, 2018)
The association of single transmembrane receptors, such as the ErbB receptors is a key event in initiating cell signaling networks. The interactions between these receptors have been well characterized for both ligand-driven and pre-formed dimers. However, the role of the membrane in modulating association is less well understood and assumes greater importance in light of altered membrane composition in diseased states. Here, we discuss how membrane composition has been observed to induce both structural and dynamic differences in receptor association. Computational studies, especially those using coarse-grain simulations have been successful in predicting the role of the membrane and calculating the related free energy landscapes. Membrane perturbations and differences in lipid chain order, related to the lipophobic effect, have been shown to play a large role in driving membrane protein association. Further, we review lipid compositions reported in diseased conditions and its effect on transmembrane receptor association, focusing on the ErbB growth factor receptor dimers in cancer. Understanding the role of the membrane in receptor association will provide general design principles driving receptor organization, as well as help to identify novel therapeutic strategies.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.

Membrane-induced organization and dynamics of the N-terminal domain of chemokine receptor CXCR1: insights from atomistic simulations - Kharche, Shalmali; Joshi, Manali; Sengupta, Durba; Chattopadhyay, Amitabha (Chemistry and Physics of Lipids, 2018)
The CXC chemokine receptor 1 (CXCR1) is an important member of the G protein-coupled receptor (GPCR) family in which the extracellular N-terminal domain has been implicated in ligand binding and selectivity. The structure of this domain has not yet been elucidated due to its inherent dynamics, but experimental evidence points toward membrane-dependent organization and dynamics. To gain molecular insight into the interaction of the N-terminal domain with the membrane bilayer, we performed a series of microsecond time scale atomistic simulations of the N-terminal domain of CXCR1 in the presence and absence of POPC bilayers. Our results show that the peptide displays a high propensity to adopt a beta-sheet conformation in the presence of the membrane bilayer. The interaction of the peptide with the membrane bilayer was found to be transient in our simulations. Interestingly, a scrambled peptide, containing the same residues in a randomly varying sequence, did not exhibit membrane-modulated structural dynamics. These results suggest that sequence-dependent electrostatics, modulated by the membrane, could play an important role in folding of the N-terminal domain. We believe that our results reinforce the emerging paradigm that cellular membranes could be important modulators of function of G protein-coupled receptors such as CXCR1.
Keywords: All atom MD simulations; beta-sheet; CXCR1; Membrane interaction; N-terminal

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding

Understanding conformational dynamics of complex lipid mixtures relevant to biology - Friedman, Ran; Khalid, Syma; Aponte-Santamaria, Camilo; Arutyunova, Elena; Becker, Marlon; Boyd, Kevin J.; Christensen, Mikkel; Coimbra, Joao T. S.; Concilio, Simona; Daday, Csaba; van Eerden, Floris J.; Fernandes, Pedro A.; et al. (Journal of membrane biology, 2018)
This is a perspective article entitled "Frontiers in computational biophysics: understanding conformational dynamics of complex lipid mixtures relevant to biology" which is following a CECAM meeting with the same name.

Actin cytoskeleton and membrane interactions: role in GPCR function and organization - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Proceedings of the Indian National Science Academy, 2019)
Cell signaling networks are generally initiated at the cell membrane and mediated by receptors such as the G proteincoupled receptors (GPCRs). Adjacent to the cell membrane lies a complex network of proteins - the actin cytoskeleton to which several structural and physiological roles have been attributed. An emerging role of the cytoskeleton is to modulate GPCR function and organization, either directly or indirectly. The GPCR-cytoskeleton cross-talk is a complex hierarchical process where each step has its own set of rules and combinations. Due to the inherent complexity involved at each step and the multiple spatio-temporal levels, a complete picture is yet to emerge. In this review article, we provide an overview of actin-membrane interactions and how they modulate GPCR function and organization.

Differential dynamics underlying the Gln27Glu population variant of the beta(2)-adrenergic receptor - Bhosale, Sumedha; Nikte, V. Siddhanta; Sengupta, Durba; Joshi, Manali (Journal of Membrane Biology, 2019)
The beta (2)-adrenergic receptor (beta (2)AR) is a membrane-bound G-protein-coupled receptor and an important drug target for asthma. Clinical studies report that the population variant Gln27Glu is associated with a differential response to common asthma drugs, such as albuterol, isoproterenol and terbutaline. Interestingly, the 27th amino acid is positioned on the N-terminal region that is the most flexible and consequently the least studied part of the receptor. In this study, we probe the molecular origin of the differential drug binding by performing structural modeling and simulations of the wild-type (Gln) and variant (Glu) receptors followed by ensemble docking with the ligands, albuterol, isoproterenol and terbutaline. In line with clinical studies, the ligands were observed to interact preferentially with the Glu variant. Our results indicate that the Glu residue at the 27th position perturbs the network of electrostatic interactions that connects the N-terminal region to the binding site in the wild-type receptor. As a result, the Glu variant is observed to bind better to the three ligands tested in this study. Our study provides a structural basis to explain the variable drug response associated with the 27th position polymorphism in the beta (2)AR and is a starting step to identify genotype-specific therapeutics.
Keywords: beta(2)-Adrenergic receptor; G-protein-coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

In vitro and in silico studies on membrane interactions of diverse Capsicum annuum flower gamma-thionin peptides - Nikte, Siddhanta; Gahankari, Apurva; Mulla, Javed; Sengupta, Durba; Joshi, Manali; Tamhane, Vaijayanti (Proteins-Structure Function and Bioinformatics, 2019)
Thionins are small, cysteine-rich peptides that play an important role in plant defense, primarily through their interactions with membranes. Eight novel gamma-thionin peptides (CanThio1-8) were isolated from the flower of Capsicum annuum. Sequence analysis revealed that the peptides cluster into three groups. A representative peptide from each group (CanThio1, 2, and 3) was used for experimental characterization. Interestingly, peptides were found to possess some cytotoxic activity against normal human embryonic kidney cell line but higher cytotoxicity against cancer cell line MCF-7. CanThio3 peptide was chosen as a representative peptide to study the molecular mechanism of action on membranes. Microsecond timescale atomistic simulations of CanThio3 were performed in the presence of a POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) lipid bilayer. Simulations revealed that CanThio3 interacts with the bilayer and causes lipid thinning in the vicinity. Nonpolar amino acids specific to the alpha-core region of CanThio3 along with nonpolar residues in the gamma-core region are seen to interact with the lipid tails. The differences in the amino acid sequence of CanThio peptides in these regions explain the variability in cytotoxic activities. In summary, our results demonstrate the membrane-mediated activity of a novel series of gamma-thionin peptides from C. annuum.
Keywords: Capsicum annuum; Cytotoxicity; gamma-thionin; MD simulations; Membrane

Interplay between membrane curvature and cholesterol: role of palmitoylated caveolin-1 - Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2019)
Caveolin-1 (cav-1) is an important player in cell signaling and endocytosis that has been shown to colocalize with cholesterol-rich membrane domains. Experimental studies with varying cav-1 constructs have suggested that it can induce both cholesterol clustering and membrane curvature. Here, we probe the molecular origin of membrane curvature and cholesterol clustering by cav-1 by using coarse-grain molecular dynamics simulations. We have performed a series of simulations of a functionally important cav-1 construct, comprising the membrane-interacting domains and a C-terminal palmitoyl tail. Our results suggest that cav-1 is able to induce cholesterol clustering in the membrane leaflet to which it is bound as well as the opposing leaflet. A positive membrane curvature is observed upon cav-1 binding in cholesterol-containing bilayers. Interestingly, we observe an interplay between cholesterol clustering and membrane curvature such that cav-1 is able to induce higher membrane curvature in cholesterol-rich membranes. The role of the cav-1 palmitoyl tail is less clear and appears to increase the membrane contacts. Further, we address the importance of the secondary structure of cav-1 domains and show that it could play an important role in membrane curvature and cholesterol clustering. Our work is an important step toward a molecular picture of caveolae and vesicular endocytosis.

Resolving the conformational dynamics of ErbB growth factor receptor dimers - Pawar, Aiswarya B.; Sengupta, Durba (Journal of Structural Biology, 2019)
The combinatorial dimerization of the ErbB growth factor receptors (ErbB(1) - ErbB(4)) are critical for their function. Here, we have characterized the conformational dynamics of ErbB transmembrane homo-dimers and hetero-dimers by using a coarse-grain simulation framework. All dimers, except ErbB (4-4) and ErbB(1-4), exhibit at least two conformations. The reported NMR structures correspond to one of these conformations, representing the N-terminal active state in ErbB(1-1) (RH2), ErbB(2-2) (RH1) and ErbB(4-4) (RH) homo-dimers and the LH dimer in ErbB(3-3) homo-dimer, validating the computational approach. Further, we predict a right-handed ErbB(4) dimer conformer that warrants experimental testing. The five hetero-dimers that have not yet been experimentally resolved display prominent right-handed dimers associating by the SmXXXSm motif. Our results provide insights into the constitutive signaling of ErbB(4) after cleavage of the extracellular region. The presence of the inactive-like dimer conformers leading to symmetric kinase domains gives clues on the autoinhibition of the receptor dimers. The dimer states characterized here represent an important step towards understanding the combinatorial cross associations in the ErbB family.
Keywords: Martini coarse-grained simulations; Membrane protein structure; Transmembrane dimer

Special issue: membrane and receptor dynamics - Prakash, Shikha; Sengupta, Durba (Journal of Membrane Biology, 2019)

Dynamic protein interfaces and conformational landscapes of membrane protein complexes - Kharche, Shalmali A.; Sengupta, Durba (Current Opinion in Structural Biology, 2020)
Dynamic interactions between membrane proteins span a range of spatio-temporal scales and determine several cellular outcomes. Experimental methods in structure determination are able to resolve static protein-protein complexes at the membrane, but lack the resolution required for disordered, flexible domains and dynamic interactions. Computational approaches could bridge the resolution gap and help to unravel molecular details underlying these crucial interactions. Here, we review current approaches to predict dynamic membrane-protein complexes, with a focus on G protein-coupled receptors (GPCRs). Ensemble coarse-grain simulations have captured the conformational heterogeneity of several membrane receptor complexes. In conjunction, the conformational plasticity of protein interfaces especially encompassing unstructured domains is well represented by atomistic simulations. A combined integrative approach will pave the way forward to understand the molecular details of these dynamic complexes.

Lipid-dependent conformational landscape of the ErbB2 growth factor receptor dimers - Gopal, Srinivasa M.; Pawar, Aiswarya B.; Wassenaar, Tsjerk A.; Sengupta, Durba (Chemistry and Physics of Lipids, 2020)
Altered lipid metabolism has been linked to cancer development and progression. Several roles have been attributed to the increased saturation and length of lipid acyl tails observed in tumors, but its effect on signaling receptors is still emerging. In this work, we have analyzed the lipid dependence of the ErbB2 growth factor receptor dimerization that plays an important role in the pathogenesis of breast cancer. We have performed coarse-grain ensemble molecular dynamics simulations to comprehensively sample the ErbB2 monomer-dimer association. Our results indicate a dynamic dimer state with a complex conformational landscape that is modulated with increasing lipid tail length. We resolve the native N-terminal ``active'' and C-terminal ``inactive'' conformations in all membrane compositions. However, the relative population of the N-terminal and C-terminal conformers is dependent on length of the saturated lipid tails. In short-tail membranes, additional non-specific dimers are observed which are reduced or absent in long-tailed bilayers. Our results indicate that the relative population as well as the structure of the dimer state is modulated by membrane composition. We have correlated these differences to local perturbations of the membrane around the receptor. Our work is an important step in characterizing ErbB dimers in healthy and diseased states and emphasize the importance of sampling lipid dynamics in understanding receptor association.
Keywords: ErbB2 dimer; Lipid effects; Martini coarse-grained simulations; Membrane protein structure; Transmembrane association

Molecular determinants of GPCR oligomerization - Mohole, Madhura; Kumar, G. Aditya; Sengupta, Durba; Chattopadhyay, Amitabha (Molecular determinants of GPCR oligomerization, 2020)

Role of cholesterol-mediated effects in GPCR heterodimers - Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha; Sengupta, Durba (Chemistry and Physics of Lipids, 2020)
G protein-coupled receptors (GPCRs) are transmembrane receptors that mediate a large number of cellular responses. The organization of GPCRs into dimers and higher-order oligomers is known to allow a larger repertoire of downstream signaling events. In this context, a crosstalk between the adenosine and dopamine receptors has been reported, indicating the presence of heterodimers that are functionally relevant. In this paper, we explored the effect of membrane cholesterol on the adenosine(2A) (A(2A)) and dopamine D-3 (D-3) receptors using coarse-grain molecular dynamics simulations. We analyzed cholesterol interaction sites on the A(2A) receptor and were able to reproduce the sites indicated by crystallography and previous atomistic simulations. We predict novel cholesterol interaction sites on the D-3 receptor that could be important in the reported cholesterol sensitivity in receptor function. Further, we analyzed the formation of heterodimers between the two receptors. Our results suggest that membrane cholesterol modulates the relative population of several co-existing heterodimer conformations. Both direct receptor-cholesterol interaction and indirect membrane effects contribute toward the modulation of heterodimer conformations. These results constitute one of the first examples of modulation of GPCR hetero-dimerization by membrane cholesterol, and could prove to be useful in designing better therapeutic strategies.
Keywords: Adenosine(2A) receptor; Cholesterol; Dopamine D-3 receptor; G protein-coupled receptors; Heterodimer; MARTINI coarse-grain simulation

Sphingomyelin effects in caveolin-1 mediated membrane curvature published as part of the journal of physical chemistry virtual special issue ``computational and experimental advances in biomembranes'' - Krishna, Anjali; Prakash, Shikha; Sengupta, Durba (Journal of Physical Chemistry B, 2020)
The caveolin-1 (cav-1) protein is an integral component of caveolae and has been reported to colocalize with cholesterol and sphingomyelin-rich curved membrane domains. Here, we analyze the molecular interactions between cav-1 and sphingomyelin containing bilayers using a series of coarse-grain simulations, focusing on lipid clustering and membrane curvature. We considered a palmitoylated-cav-1 construct interacting with phospholipid/cholesterol membranes with asymmetrically distributed sphingomyelin, varying between 5 and 15% in total. We observe that cav-1 binds to the intracellular leaflet and induces a small positive curvature in the leaflet to which it is bound and an opposing negative curvature in the extracellular leaflet. Both cholesterol and sphingomyelin are observed to cluster in cav-1 bound membranes, mainly in the extracellular leaflet. Due to their negative spontaneous curvature, clustering of cholesterol and sphingomyelin facilitates membrane curvature such that the extent of either cholesterol or sphingomyelin clustering is dependent on the curvature induced. Our results suggest that cav-1 binding induces concentration-dependent curvature effects in sphingomyelin-rich membranes. Overall, our work is an important step in understanding the molecular basis of curvature and lipid clustering in cav1 bound cellular membranes.

Caveolin induced membrane curvature and lipid clustering: two sides of the same coin? - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Faraday Discussions, 2021)
Caveolin-1 (cav-1) is a multi-domain membrane protein that is a key player in cell signaling, endocytosis and mechanoprotection. It is the principle component of cholesterol-rich caveolar domains and has been reported to induce membrane curvature. The molecular mechanisms underlying the interactions of cav-1 with complex membranes, leading to modulation of membrane topology and the formation of cholesterol-rich domains, remain elusive. In this study, we aim to understand the effect of lipid composition by analyzing the interactions of cav-1 with complex membrane bilayers comprised of about sixty lipid types. We have performed a series of coarse-grain molecular dynamics simulations using the Martini force-field with a cav-1 protein construct (residue 82-136) that includes the membrane binding domains and a palmitoyl tail. We observe that cav-1 induces curvature in this complex membrane, though it is restricted to a nanometer length scale. Concurrently, we observe a clustering of cholesterol, sphingolipids and other lipid molecules leading to the formation of nanodomains. Direct microsecond timescale interactions are observed for specific lipids such as cholesterol, phosphatidylserine and phosphatidylethanolamine lipid types. The results indicate that there is an interplay between membrane topology and lipid species. Our work is a step toward understanding how lipid composition and organization regulate the formation of caveolae, in the context of endocytosis and cell signaling.

Caveolin mediated curvature and clustering: from simple to complex membrane - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2021)

Conformational plasticity and dynamic interactions of the N-terminal domain of the chemokine receptor CXCR1 - Kharche, Shalmali; Joshi, Manali; Chattopadhyay, Amitabha; Sengupta, Durba (Plos Computational Biology, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The dynamic interactions between G protein-coupled receptors (GPCRs) and their cognate protein partners are central to several cell signaling pathways. For example, the association of CXC chemokine receptor 1 (CXCR1) with its cognate chemokine, interleukin-8 (IL8 or CXCL8) initiates pathways leading to neutrophil-mediated immune responses. The N-terminal domain of chemokine receptors confers ligand selectivity, but unfortunately the conformational dynamics of this intrinsically disordered region remains unresolved. In this work, we have explored the interaction of CXCR1 with IL8 by microsecond time scale coarse-grain simulations, complemented by atomistic models and NMR chemical shift predictions. We show that the conformational plasticity of the apo-receptor N-terminal domain is restricted upon ligand binding, driving it to an open C-shaped conformation. Importantly, we corroborated the dynamic complex sampled in our simulations against chemical shift perturbations reported by previous NMR studies and show that the trends are similar. Our results indicate that chemical shift perturbation is often not a reporter of residue contacts in such dynamic associations. We believe our results represent a step forward in devising a strategy to understand intrinsically disordered regions in GPCRs and how they acquire functionally important conformational ensembles in dynamic protein-protein interfaces.

Dynamic coupling analysis on plant sesquiterpene synthases provides leads for the identification of product specificity determinants - Singh, Sneha; Thulasiram, V, Hirekodathakallu; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2021)
Sesquiterpene synthases catalyse cyclisation of farnesyl pyrophosphate to produce diverse sesquiterpenes. Despite utilising the same substrate and exhibiting significant sequence and structural homology, these enzymes form different products. Previous efforts were based on identifying the effect of divergent residues present at the catalytic binding pocket on the product specificity of these enzymes. However, the rationales deduced for the product specificity from these studies were not generic enough to be applicable to other phylogenetically distant members of this family. To address this problem, we have developed a novel approach combining sequence, structural and dynamical information of plant sesquiterpene synthases (SSQs) to predict product modulating residues (PMRs). We tested this approach on the SSQs with known PMRs and also on sesquisabinene synthase 1 (SaSQS1), a SSQ from Indian sandalwood. Our results show that the dynamical sectors of SSQs obtained from molecular dynamics simulation and their hydrophobicity and vicinity indices together provide leads for the identification of PMRs. The efficacy of the technique was tested on SaSQS1 using mutagenesis. To the best of our knowledge, this is a first technique of this kind which provides cues on PMRs of SSQs, with divergent phylogenetic relationship. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: molecular dynamics; Product specificity; Sesquiterpene synthases; Statistical coupling analysis; X-ray crystallography

Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Molecular interplay at the membrane and impact on cellular physiology - Pucadyil, Thomas; Kulkarni, Kiran; Sengupta, Durba (Journal of Membrane Biology, 2021)

Rise of the superbugs: what we need to know overview of antimicrobial resistance - Sengupta, Durba; Raghunathan, Anu (Resonance, 2021)
Bacteria often cause infections, and we take antibiotics to help us recover. Antibiotics are like magic pills that have saved millions of lives. However, the overuse of antibiotics is now making bacteria evolve fast and evade these antibiotics. A few bacteria like the purple one in the petri plate (Figure 1) have evolved a way to dodge and not get killed by one particular kind of antibiotic. The day might come soon when not a single antibiotic would work, and we could die of even tiny paper cuts. In this article, we discuss what antibiotics are, how they target bacteria, and why bacteria are suddenly becoming resistant to antibiotics. We include a list of ten points that each of us must follow and a pledge for everyone to take, to help stop the spread of antibiotic resistance. A small questionnaire is included that we would like you all to answer. Together we can win the battle against antibiotic resistance.

Role of cholesterol in transmembrane dimerization of the ErbB2 growth factor receptor - Pawar, Aiswarya B.; Sengupta, Durba (Journal of Membrane Biology, 2021)
The association of ErbB2 growth factor receptors is critical for cell growth and potentiates tumor proliferation in several cancer types. An important aspect in ErbB2 association is the role of lipids such as cholesterol, especially since their metabolism is often reprogrammed in cancer cells. Here, we have coupled metadynamics with coarse-grain simulations to identify cholesterol effects in the transmembrane dimerization of ErbB2 receptors. Overall, cholesterol interactions are observed with the receptor that directly tunes the association energetics. Several dimer conformations are identified both in the presence and absence of cholesterol, although the dimer regime appears to be more favorable in the presence of cholesterol. We observe an overall modulation of the underlying energy profile and the symmetric active and inactive conformational states are not distinguished in the presence of cholesterol. We show that cholesterol binds to the receptor transmembrane domain at a site (CRAC motif) that overlaps with the dimer interface (SmXXXSm motif). The competition between the transmembrane interactions and cholesterol interactions decides the final conformational landscape. Our work is an important step toward characterizing cholesterol effects in ErbB2 membrane receptor function. [GRAPHICS] .
Keywords: Cholesterol; ErbB2 growth factor receptor; Her2 dimer; Juxtamembrane dimer; Martini coarse-grain simulations; Metadynamics

Water mediated allosteric network in beta 2AR T164I variant modulates agonist binding affinity - Nikte, Siddhanta V.; Sonar, Krushna; Tandale, Aditi; Sengupta, Durba; Joshi, Manali (European Biophysics Journal with Biophysics Letters, 2021)

Allosteric modulation of the chemokine receptor-chemokine CXCR4-CXCL12 complex by tyrosine sulfation - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (International Journal of Biological Macromolecules, 2022)
The chemokine receptor CXCR4 and its cognate ligand CXCL12 mediate pathways that lead to cell migration and chemotaxis. Although the structural details of related receptor-ligand complexes have been resolved, the roles of the N-terminal domain of the receptor and post-translational sulfation that are determinants of ligand selectivity and affinity remain unclear. Here, we analyze the structural dynamics induced by receptor sulfation by combining molecular dynamics, docking and network analysis. The sulfotyrosine residues, 7YsN-term, 12Ys(N-term) and 21Ys(N-term) allow the N-terminal domain of the apo-sulfated receptor to adopt an ``open `` conformation that appears to facilitate ligand binding. The overall topology of the CXCR4-CXCL12 complex is independent of the sulfation state, but an extensive network of protein-protein interactions characterizes the sulfated receptor, in line with its increased ligand affinity. The altered interactions of sulfotyrosine residues, such as 21Ys(N-term)- 47R(CXCL12) replacing the 21Y(N-term)-13F(CXCL12) interaction, propagate via allosteric pathways towards the receptor lumen. In particular, our results suggest that the experimentally-reported receptor-ligand interactions 262D(6.58)- 8R(CXCL12) and 277E(7.28)-12R(CXCL12) could be dependent on the sulfation state of the receptor and need to be carefully analyzed. Our work is an important step in understanding chemokine-receptor interactions and how post-translational modifications could modulate receptor-ligand complexes.
Keywords: Allosteric communication pathway; Atomistic molecular dynamics simulations; G protein-coupled receptor; Ligand binding; Post-translational modification; Protein-protein interface

Copper(II) import and reduction are dependent on His-Met clusters in the extracellular amino terminus of human copper transporter-1 - Kar, Sumanta; Sen, Samarpita; Maji, Saptarshi; Saraf, Deepashri; Ruturaj; Paul, Rupam; Dutt, Sohini; Mondal, Basudeb; Rodriguez-Boulan, Enrique; Schreiner, Ryan; Sengupta, Durba; Gupta, Arnab (Journal of Biological Chemistry, 2022)
Copper(I) is an essential metal for all life forms. Though Cu(II) is the most abundant and stable state, its reduction to Cu(I) via an unclear mechanism is prerequisite for its bioutilization. In eukaryotes, the copper transporter-1(CTR1) is the primary high-affinity copper importer, although its mechanism and role in Cu(II) reduction remain uncharacterized. Here we show that extracellular amino-terminus of human CTR1 contains two methionine-histidine clusters and neighboring aspartates that distinctly bind Cu(I) and Cu(II) preceding its import. We determined that hCTR1 localizes at the basolateral membrane of polarized MDCK-II cells and that its endocytosis to Common-Recycling-Endosomes is regulated by reduction of Cu(II) to Cu(I) and subsequent Cu(I) coordination by the methionine cluster. We demonstrate the transient binding of both Cu(II) and Cu(I) during the reduction process is facilitated by aspartates that also act as another crucial determinant of hCTR1 endocytosis. Mutating the first Methionine cluster ((7)Met-Gly-Met(9)) and Asp(13)( )abrogated copper uptake and endocytosis upon copper treatment. This phenotype could be reverted by treating the cells with reduced and nonreoxidizable Cu(I). We show that histidine clusters, on other hand, bind Cu(II) and are crucial for hCTR1 functioning at limiting copper. Finally, we show that two N-terminal His-Met-Asp clusters exhibit functional complementarity, as the second cluster is sufficient to preserve copper-induced CTR1 endocytosis upon complete deletion of the first cluster. We propose a novel and detailed mechanism by which the two His-Met-Asp residues of hCTR1 amino-terminus not only bind copper, but also maintain its reduced state, crucial for intracellular uptake.

Graphical Biology Insights into the dynamic interactions at chemokine-receptor interfaces and mechanistic models of chemokine binding - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (Journal of Structural Biology, 2022)
Chemokine receptors are the central signaling hubs of several processes such as cell migration, chemotaxis and cell positioning. In this graphical review, we provide an overview of the structural and mechanistic principles governing chemokine recognition that are currently emerging. Structural models of chemokine-receptor cocomplexes with endogenous chemokines, viral chemokines and therapeutics have been resolved that highlight multiple interaction sites, termed as CRS1, CRS1.5 etc. The first site of interaction has been shown to be the Nterminal domain of the receptors (CRS1 site). A large structural flexibility of the N-terminal domain has been reported that was supported by both experimental and simulation studies. Upon chemokine binding, the Nterminal domain appears to show constricted dynamics and opens up to interact with the chemokine via a large interface. The subsequent sites such as CRS1.5 and CRS2 sites have been structurally well resolved although differences arise such as the localization of the N-terminus of the ligand to a major or minor pocket of the orthosteric binding site. Several computational studies have highlighted the dynamic protein-protein interface at the CRS1 site that seemingly appears to resolve the differences in NMR and mutagenesis studies. Interestingly, the differential dynamics at the CRS1 site suggests a mixed model of binding with complex signatures of both conformational selection and induced fit models. Integrative experimental and computational approaches could help unravel the structural basis of promiscuity and specificity in chemokine-receptor binding and open up new avenues of therapeutic design.
Keywords: Chemokine receptors; GPCRs; Intrinsically disordered protein domains; protein-protein interactions

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.

Molecular determinants of GPCR pharmacogenetics: deconstructing the population variants in β2-adrenergic receptor - Joshi, Manali; Nikte, Siddhanta; Sengupta, Durba (Advances in Protein Chemistry and Structural Biology, 2022)
G protein-coupled receptors (GPCRs) are membrane proteins that play a central role in cell signaling and constitute one of the largest classes of drug targets. The molecular mechanisms underlying GPCR function have been characterized by several experimental and computational methods and provide an understanding of their role in physiology and disease. Population variants arising from nsSNPs affect the native function of GPCRs and have been implicated in differential drug response. In this chapter, we provide an overview on GPCR structure and activation, with a special focus on the β2-adrenergic receptor (β2-AR). First, we discuss the current understanding of the structural and dynamic features of the wildtype receptor. Subsequently, the population variants identified in this receptor from clinical and large-scale genomic studies are described. We show how computational approaches such as bioinformatics tools and molecular dynamics simulations can be used to characterize the variant receptors in comparison to the wildtype receptor. In particular, we discuss three examples of clinically important variants and discuss how the structure and function of these variants differ from the wildtype receptor at a molecular level. Overall, the chapter provides an overview of structure and function of GPCR variants and is a step towards the study of inter-individual differences and personalized medicine.

Molecular mechanisms underlying caveolin-1 mediated membrane curvature - Prakash, Shikha; Malshikare, Hrushikesh; Sengupta, Durba (Journal of Membrane Biology, 2022)
Caveolin-1 is one of the main protein components of caveolae that acts as a mechanosensor at the cell membrane. The interactions of caveolin-1 with membranes have been shown to lead to complex effects such as curvature and the clustering of specific lipids. Here, we review the emerging concepts on the molecular interactions of caveolin-1, with a focus on insights from coarse-grain molecular dynamics simulations. Consensus structural models of caveolin-1 report a helix-turn-helix core motif with flanking domains of higher disorder that could be membrane composition dependent. Caveolin-1 appears to be mainly surface-bound and does not embed very deep in the membrane to which it is bound. The most interesting aspect of caveolin-1 membrane binding is the interplay of cholesterol clustering and membrane curvature. Although cholesterol has been reported to cluster in the vicinity of caveolin-1 by several approaches, simulations show that the clustering is maximal in membrane leaflet opposing the surface-bound caveolin-1. The intrinsic negative curvature of cholesterol appears to stabilize the negative curvature in the opposing leaflet. In fact, the simulations show that blocking cholesterol clustering (through artificial position restraints) blocks membrane curvature, and vice versa. Concomitant with cholesterol clustering is sphingomyelin clustering, again in the opposing leaflet, but in a concentration-dependent manner. The differential stress due to caveolin-1 binding and the inherent asymmetry of the membrane leaflets could be the determinant for membrane curvature and needs to be further probed. The review is an important step to reconcile the molecular level details emerging from simulations with the mesoscopic details provided by state of the art experimental approaches. [GRAPHICS] .
Keywords: Cholesterol clustering; Membrane curvature; Protein-lipid interactions

Preface to special issue on protein-mediated membrane remodeling - Chakraborty, Hirak; Sengupta, Durba (Journal of Membrane Biology, 2022)

Substrate induced dynamical remodeling of the binding pocket generates GTPase specificity in DOCK family of guanine nucleotide exchange factors - Roy, Debopriya; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2022)
Dedicator of cytokinesis (DOCK) family of guanine nucleotide exchange factors (GEFs) activate two members of Rho family GTPases, Rac1/Cdc42, to exert diverse cellular processes, including cell migration. As DOCK GEFs have been critically implicated in tumour cell migration, understanding their function and specificity is imperative for designing anti-metastatic drugs. Based on their GTPase specificity they have been classified as Rac, Cdc42 and dual specific GEFs. Despite extensive structural studies, the factors that determine GTPase specificity of DOCK GEFs have remained elusive. Here, we show that subtle dynamical coupling between GEF and GTPase structures modulate the binding interface to generate mutual spec-ificity. To cluster the dynamically coupled residues in GEF-GTPase complexes a novel intra-residue backbone-torsion-angles based mutual information (TMI) technique was employed. TMI was calcu-lated from 4500 trajectories obtained from a total of 4.5ms molecular dynamics simulations performed on members of all the three clades of DOCK GEFs. The obtained clusters suggest a specificity generation mechanism that involves optimization of the binding pocket for the crucial divergent residue at the 56th position of Rac/Cdc42 (FCdc42/WRac1). These clusters encompass five residues from the structural segment lobe C -a10 helix of the DOCK proteins and functional SWI region of GTPase, which induce orchestrated structural modulations to generate the specificity. Even the conserved residues from SWI region are seen to augment the specificity defining dynamical rearrangements. Furthermore, the pro-posed dynamical GTPase-DOCK GEF specificity model was verified using mutagenesis studies on Rac1 and dual GTPase specific Dock2 and Dock6, respectively. Thus the current study provides the generic substrate specificity determinants of DOCK GEFs, which are not apparent from the conventional struc-tural analysis.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Dedicator of cytokinesis; GTPase specificity; Guanine exchange factors; Molecular dynamics simulations; Mutual information; Rho GTPases

Synergistic and competitive lipid interactions in the serotonin1A receptor microenvironment - Mohole, Madhura; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2022)
The interaction of lipids with G-protein-coupled receptors (GPCRs) has been shown to modulate and dictate several aspects of GPCR organization and function. Diverse lipid interaction sites have been identified from structural biology, bioinformatics, and molecular dynamics studies. For example, multiple cholesterol interaction sites have been identified in the serotonin1A receptor, along with distinct and overlapping sphingolipid interaction sites. How these lipids interact with each other and what is the resultant effect on the receptor is still not clear. In this work, we have analyzed lipid-lipid crosstalk at the receptor of the serotonin1A receptor embedded in a membrane bilayer that mimics the neuronal membrane composition by long coarse-grain simulations. Using a set of similarity coefficients, we classified lipids that bind at the receptor together as synergistic cobinding, and those that bind individually as competitive. Our results show that certain lipids interact with the serotonin1A receptor in synergy with each other. Not surprisingly, the ganglioside GM1 and cholesterol show a synergistic cobinding, along with the relatively uncommon GM1-phosphatidylethanolamine (PE) and cholesterol-PE synergy. In contrast, certain lipid pairs such as cholesterol and sphingomyelin appear to be in competition at several sites, despite their coexistence in lipid nanodomains. In addition, we observed intralipid competition between two lipid tails, with the receptor exhibiting increased interactions with the unsaturated lipid tails. We believe our work represents an important step in understanding the diversity of GPCR-lipid interactions and exploring synergistic cobinding and competition in natural membranes.
Keywords: GPCR; lipid crosstalk; Martini coarse-grain simulations; Membrane cholesterol; neuronal membranes

Cofilin-membrane interactions: electrostatic effects in phosphoinositide lipid binding - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (ChemPhysChem, 2023)
The actin cytoskeleton interacts with the cell membrane primarily through the indirect interactions of actin-binding proteins such as cofilin-1. The molecular mechanisms underlying the specific interactions of cofilin-1 with membrane lipids are still unclear. Here, we performed coarse-grain molecular dynamics simulations of cofilin-1 with complex lipid bilayers to analyze the specificity of protein-lipid interactions. We observed the maximal interactions with phosphoinositide (PIP) lipids, especially PIP2 and PIP3 lipids. A good match was observed between the residues predicted to interact and previous experimental studies. The clustering of PIP lipids around the membrane bound protein leads to an overall lipid demixing and gives rise to persistent membrane curvature. Further, through a series of control simulations, we observe that both electrostatics and geometry are critical for specificity of lipid binding. Our current study is a step towards understanding the physico-chemical basis of cofilin-PIP lipid interactions.
Keywords: complex membrane; lipid clustering; Martini coarse-grain simulations; Molecular dynamics simulations; Protein-lipid interactions

Differential membrane curvature induced by distinct protein conformers - Malshikare, Hrushikesh; Prakash, Shikha; Sengupta, Durba (Soft Matter, 2023)
Membrane topology changes are associated with various cellular processes and are modulated by synergistic effects between lipid composition and membrane-associated proteins. However, how protein shape or conformational dynamics couples to membrane molecular properties remains unclear. In this work, we aim to investigate this coupling behavior using the curvature-inducing protein caveolin-1. We considered distinct protein conformers of the helical hairpin protein corresponding to different protein shapes, such as the wedge and the banana-shaped conformers. The different protein conformers were simulated in a coarse-grain representation in the presence of cholesterol-sphingomyelin rich membrane. We observed that membrane curvature is dependent on protein shape and is the lowest for the wedge conformer and maximal for the banana conformer. The differences in the net stress between the two membrane leaflets, calculated from the lateral pressure profile distributions in lipid bilayers for different protein conformers, show a similar trend. In conjunction, we show that cholesterol and sphingomyelin clustering in the membrane is modulated by protein shape. Overall, our results provide molecular-level insights into the coupling between membrane topology, protein shape and lipid clustering in cell membranes.

Molecular mechanisms underlying nanowire formation in pristine phthalocyanine - Pinjari, Aadil; Saraf, Deepashri; Sengupta, Durba (Physical Chemistry Chemical Physics, 2023)
Understanding the molecular processes of nanowire self-assembly is crucial for designing and controlling nanoscale structures that could lead to breakthroughs in functional materials. In this work, we focus on pristine phthalocyanines as a representative example of mesogenic supramolecular assemblies and have analyzed the formation of nanowires using classical molecular dynamics simulations. In the simulations, the molecules spontaneously form multi-columnar structures resembling supramolecular polymers that subsequently grow into more ordered aggregates. These self-assemblies are concentration dependent, leading to the formation of multi-columnar, dynamic aggregates at higher concentrations and nanowires at lower concentrations. The multi-columnar assemblies on a whole are more disordered than the nanowires, but have locally ordered domains of parallel facing molecules that can fluctuate while maintaining their overall shape. The nanowire formation at lower concentrations involves the initial interaction and clustering of randomly oriented phthalocyanine molecules, followed by the merging of small clusters into elongated segments and the eventual formation of a stable nanowire. We observe three main conformers in these self-assemblies, the parallel, T-shaped and edge-to-edge stacking of the phthalocyanine dimers. We calculate the underlying free energy landscape and show that the parallel conformers form the most stable configuration which is followed by the T-shaped and edge-to-edge dimer configurations. The findings provide insights into the mechanisms and pathways of nanowire formation and a step towards the understanding of self-assembly processes in supramolecular mesogens. Understanding the molecular processes of nanowire self-assembly of phthalocyanine molecules.

Palmitoylation of the glucagon-like peptide-1 receptor modulates cholesterol interactions at the receptor-lipid microenvironment - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Journal of Physical Chemistry B, 2023)
The G protein-coupled receptor (GPCR) superfamily of cell surface receptors has been shown to be functionally modulated by post-translational modifications. The glucagon-like peptide receptor-1 (GLP-1R), which is a drug target in diabetes and obesity, undergoes agonist-dependent palmitoyl tail conjugation. The palmitoylation in the C-terminal domain of GLP-1R has been suggested to modulate the receptor-lipid microenvironment. In this work, we have performed coarse-grain molecular dynamics simulations of palmitoylated and nonpalmitoylated GLP-1R to analyze the differential receptor-lipid interactions. Interestingly, the placement and dynamics of the C-terminal domain of GLP-1R are found to be directly dependent on the palmitoyl tail. We observe that both cholesterol and phospholipids interact with the receptor but display differential interactions in the presence and absence of the palmitoyl tail. We characterize important cholesterol-binding sites and validate sites that have been previously reported in experimentally resolved structures of the receptor. We show that the receptor acts like a conduit for cholesterol flip-flop by stabilizing cholesterol in the membrane core. Taken together, our work represents an important step in understanding the molecular effects of lipid modifications in GPCRs.

Surface-induced demixing of self-assembled isomeric mixtures of citral - Saraf, Deepashri; Prakash, Shikha; Pinjari, Aadil; Pujari, Bhalchandra; Sengupta, Durba (Journal of Molecular Liquids, 2023)
The self-assembly of organic molecules and their interactions with metal surfaces have been of considerable interest, both for developing novel functional materials and for understanding fundamental design principles of nanostructures. In this study, we investigate the solution and surface-induced self-assembly of two stereoisomers of citral molecules (geranial and neral) using atomistic molecular dynamics simulations. We demonstrate that the morphology of the aggregates in water is concentration dependent (ranging from distorted spherical to slab-like aggregates) but independent of isomer effects. The isomeric mixtures of citral indicate homogeneous mixing based on differential density maps and high values of Shannon entropy. Interestingly, surface-confinement of citral aggregates on a Cu(111) surface leads to phase segregation and demixing of the two isomers that is more apparent in the surface-bound monolayer in comparison to the adjacent layers. Positional ordering and formation of domains are observed over a series of isomeric citral mixtures with varying compositions, as indicated by high differential density and low values of Shannon entropy. Our work provides new insights into molecular self-assembly of organic molecules in nanostructures and metal-organic overlayers.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Citral; Isomers; Metal-organic interactions; molecular dynamics; Self-assembly; Shannon entropy

Wavelet coherence phase analysis decodes the universal switching mechanism of Ras GTPase superfamily - Motiwala, Zenia; Sandholu, Anand S.; Sengupta, Durba; Kulkarni, Kiran (iScience, 2023)
The Ras superfamily of GTPases regulate critical cellular processes by shuttling between GTP-bound ON and GDP-bound OFF states. This switching mechanism is attributed to the conformational changes in two loops, SWI and SWII, upon GTP binding and hydrolysis. Since these conformational changes vary across the Ras superfamily, there is no generic parameter to define their functional states. A unique wavelet coherence (WC) analysis-based approach developed here shows that the structural changes in switch regions could be mapped onto the wavelet coherence phase couplings (WPCs). Thus, WPCs could serve as unique parameters to define their functional states. Disentanglement of WPCs in oncogenic GTPases shows how breakdown of structural allostery leads to their aberrant function. These observations stand out even for simulated ensemble of switch region conformers. Overall, for the first time, we show that WPCs could unravel the latent structural deviations in Ras proteins to decode their universal switching mechanism.

Cell based assay using virus-like particles to screen AM type mimics for SARS-CoV-2 neutralisation - Gaur, Neeraj Kailash; Urankar, Shreegauri; Sengupta, Durba; Chepuri, V. Ramana; Makde, Ravindra D.; Kulkarni, Kiran (BIOCHEMICAL AND BIOPHYSICAL RESEARCH COMMUNICATIONS, 2024)
Keywords: MINIPROTEINS

Characterization of the conformational hotspots of the RNA-dependent RNA polymerase complex identifies a unique structural malleability of nsp8 - Gharui, Sowmomita; Sengupta, Durba; Das, Atanu (Journal of Physical Chemistry B, 2024)
Several antiviral therapeutic approaches have been targeted toward the RNA-dependent RNA polymerase (RdRp) complex that is involved in viral genome replication. In SARS-CoV-2, although the RdRp is a multiprotein complex, the focus has been on the ligand binding catalytic core (nonstructural protein nsp12), and not the multiprotein functional dynamics. In this study, we focus on the conformational ensembles of the RdRp complex and their modulation by the presence of RNA, performing comprehensive microsecond-scale atomistic simulations of the apo- and RNA-bound complex. We delineate the differential impact of RNA on the constituent proteins, such as conformational polymorphisms, dominant segment-specific fluctuations, and the switch in dynamical crosstalk within the complex. We distinguish dynamical signatures of nsp7, nsp8, and nsp12 in the apo-state that are reduced in the presence of the RNA and appear to ``prime'' the complex for activity. Importantly, we identify a unique structural malleability of the nsp8 protein with high conformational heterogeneity in the apo state, especially at three sites (Y71 for nsp8A, and D52 and A66 for nsp8B). Our work highlights the functional implications of the polymorphism of nsp8 structures and reveals possibilities for the development of allosteric inhibitors.

Effect of citral partitioning on structural and mechanical properties of lipid membranes - Saraf, Deepashri; Porte, Sudha; Sengupta, Durba (European Physical Journal-Special Topics, 2024)
Delineating the interactions of cellular metabolites with lipid membranes and their effects on membrane physical and mechanical properties constitutes a key step for comprehensively understanding their biological function. The plant metabolite-citral is widely used in biotechnological and cosmeceutical processes, but significant gaps remain in our understanding of how it affects cellular membranes that it interacts with. In this study, we unravel the molecular mechanisms underlying the interactions of citral with compositionally distinct model membranes using atomistic molecular dynamics simulations. Specifically, we investigate two distinct membrane compositions: the neutral phosphatidylcholine-phosphatidylethanolamine (DOPC:DOPE) bilayer, representing mammalian cell membranes and the anionic phosphatidylcholine-phosphatidylglycerol (DOPC:DOPG) bilayer, mimicking bacterial cell membranes. Our simulations reveal that citral molecules readily partition into both membranes without distinct composition-dependent effects. Monomeric citral molecules localize mainly at the interface of the acyl chain region of the lipids, and a few translocation events are sampled in the simulations. Interestingly, we observe small differences in lipid fluidity although the citral molecules significantly influence the rigidity of lipid bilayers, and a higher bending modulus was observed in DOPC:DOPE lipid bilayers compared to DOPC:DOPG bilayers. Further, citral partitioning induces an increased tendency for lipid demixing in DOPC:DOPE membranes, as evidenced by the decreased values of the Shannon entropy. Our work is an important step to elucidate the molecular processes that underlie the differential impact of cell metabolites on compositionally distinct lipid membranes.

Improved protein dynamics and hydration in the martini3 coarse-grain model - Kharche, Shalmali; Yadav, Manjul; Hande, Vrushali; Prakash, Shikha; Sengupta, Durba (Journal of Chemical Information and Modelling, 2024)
The Martini coarse-grain force-field has emerged as an important framework to probe cellular processes at experimentally relevant time- and length-scales. However, the recently developed version, the Martini3 force-field with the implemented Go model (Martini3Go), as well as previous variants of the Martini model have not been benchmarked and rigorously tested for globular proteins. In this study, we consider three globular proteins, ubiquitin, lysozyme, and cofilin, and compare protein dynamics and hydration with observables from experiments and all-atom simulations. We show that the Martini3Go model is able to accurately model the structural and dynamic features of small globular proteins. Overall, the structural integrity of the proteins is maintained, as validated by contact maps, radii of gyration (Rg), and SAXS profiles. The chemical shifts predicted from the ensemble sampled in the simulations are consistent with the experimental data. Further, a good match is observed in the protein-water interaction energetics, and the hydration levels of the residues are similar to atomistic simulations. However, the protein-water interaction dynamics is not accurately represented and appears to depend on the protein structural complexity, residue specificity, and water dynamics. Our work is a step toward testing and assessing the Martini3Go model and provides insights into future efforts to refine Martini models with improved solvation effects and better correspondence to the underlying all-atom systems.

Probing the energy landscape of the lipid interactions of the serotonin 1A receptor - Mohole, Madhura; Naglekar, Amit; Sengupta, Durba; Chattopadhyay, Amitabha (Biophysical Chemistry, 2024)
G protein-coupled receptors (GPCRs) are lipid-regulated transmembrane proteins that play a central role in cell signaling and pharmacology. Although the role of membrane lipids in GPCR function is well established, the underlying GPCR-lipid interactions have not been thermodynamically characterized due to the complexity of these interactions. In this work, we estimate the energetics and dynamics of lipid association from coarse-grain simulations of the serotonin1A receptor embedded in a complex membrane. We show that lipids bind to the receptor with varying energetics of 1-4 kT, and timescales of 1-10 mu s. The most favorable energetics and longest residence times are observed for cholesterol, glycosphingolipid GM1, phosphatidylethanolamine (PE) and phosphatidylserine (PS) lipids. Multi-exponential fitting of the contact probability suggests distinct dynamic regimes, corresponding to ps, ns and mu s timescales, that we correlate with the annular, intermediate and nonannular lipid sites. The timescales of lipid binding correspond to high barrier heights, despite their relatively weaker energetics. Our results highlight that GPCR-lipid interactions are driven by both thermodynamic interactions and the dynamical features of lipid binding.
Keywords: GPCR-lipid interactions; Lipid energetics; Lipid residence time; Molecular dynamics simulations; Serotonin 1 a receptor

State-dependent dynamics of extramembrane domains in the β2-adrenergic receptor - Nikte, Siddhanta V.; Joshi, Manali; Sengupta, Durba (Proteins- Structure Function and Bioinformatics, 2024)
G protein-coupled receptors (GPCRs) are membrane-bound signaling proteins that play an essential role in cellular signaling processes. Due to their intrinsic function of transmitting internal signals in response to external cues, these receptors are adapted to be highly dynamic in nature. The beta(2)-adrenergic receptor (beta 2AR) is a representative member of the family that has been extensively analyzed in terms of its structure and activation. Although the structure of the transmembrane domain has been characterized in the different functional states of the receptor, the conformational dynamics of the extramembrane domains, especially the intrinsically disordered regions are still emerging. In this study, we analyze the state-dependent dynamics of extramembrane domains of beta(2)AR using atomistic molecular dynamics simulations. We introduce a parameter, the residue excess dynamics that allows us to better quantify receptor dynamics. Using this measure, we show that the dynamics of the extramembrane domains are sensitive to the receptor state. Interestingly, the ligand-bound intermediate R' state shows the maximal dynamics compared to either the active R*G or inactive R states. Ligand binding appears to be correlated with high residue excess dynamics that are dampened upon G protein coupling. The intracellular loop-3 (ICL3) domain has a tendency to flip towards the membrane upon ligand binding, which could contribute to receptor ``priming.'' We highlight an important ICL1-helix-8 interplay that is broken in the ligand-bound state but is retained in the active state. Overall, our study highlights the importance of characterizing the functional dynamics of the GPCR loop domains.
Keywords: allosteric pathway; beta-2 adrenergic receptor; extramembrane domains; GPCR; loop dynamics; protein dynamics; protein network

Anomalous membrane organization by omega-6 and omega-9 fatty acids - Porte, Sudha; Pandia, Swaratmika; Joardar, Ankita; Saraf, Deepashri; Pinjari, Aadil; Chakraborty, Hirak; Sengupta, Durba (Physical Chemistry Chemical Physics, 2025)
Omega fatty acids are currently being marketed as healthy food supplements as they have been implicated in multiple pathophysiological conditions, such as reducing plaque formation of A beta peptide and inhibiting SARS-CoV-2 infection. Their mode of action has been hypothesized to be via membrane reorganization by the unsaturated acyl chains, leading to the modulation of lipid-protein cross-talk. However, the lack of molecular details led us to evaluate the molecular effect of omega-6 (linolenic acid) and omega-9 (oleic acid) fatty acids on membrane organization using a consolidated approach of fluorescence spectroscopy and all-atom molecular dynamics simulation. Our results show that the effect of these omega fatty acids is sensitive to their protonation states. Contrary to the accepted notion that chain unsaturation causes membrane disordering, both experimental and simulation results demonstrate that protonated linoleic acid promotes membrane ordering, despite having two unsaturations at the fatty acyl chain. However, protonated oleic fatty acid, with reduced unsaturation, disordered the acyl chain area of the lipid membranes. Equally surprisingly, deprotonated oleic acid orders, whereas deprotonated linoleic acid disorders, the membrane core region. Interestingly, while the lipid order parameter measurements from simulations did not capture these subtle differences, the calculated rotational autocorrelation function of a membrane dye was in line with experimentally measured apparent rotational correlation times. Our work provides a comprehensive revised molecular picture of the effect of omega fatty acids on membranes and highlights the importance of rigorous comparative approaches, as experimental and simulation studies in isolation can sometimes lead to inconsistent results.

Benchmarking a dual-scale hybrid simulation framework for small globular proteins combining the CHARMM36 and Martini2 models - Yadav, Manjul; Kharche, Shalmali; Prakash, Shikha; Sengupta, Durba (Journal of Molecular Graphics & Modelling, 2025)
Multi-scale models in which varying resolutions are considered in a single molecular dynamics simulation setup are gaining importance in integrative modeling. However, combining atomistic and coarse-grain resolutions, especially for coarse-grain force fields derived from top-down approaches, have not been well explored. In this study, we have implemented and tested a dual-resolution simulation approach to model globular proteins in atomistic detail (represented by the CHARMM36 model) with the surrounding solvent in Martini2 coarse-grain detail. The hybrid scheme considered is an extension of a model implemented earlier for mainly lipid and water molecules. We have considered a set of small globular proteins and have extensively compared to atomistic benchmark simulations as well as a host of experimental observables. We show that the protein structural dynamics sampled in the hybrid scheme is robust, and the intra-protein contact maps are reproduced, despite increased fluctuations of the loop regions. A good match is observed with experimental small angle X-ray scattering (SAXS) and NMR observables, such as chemical shifts and (3)J((HN-H alpha))-coupling, with the best match obtained for the chemical shifts. However, deviations are observed in the water dynamics and protein-water interactions which we attribute to the limitation of solvent screening in the coarse-grain force field. The computational speed-up achieved is about 2-3 times compared to an all-atom system. Overall, the hybrid model is able to retain the main features of the underlying atomistic conformational landscape with a two-fold speed-up in computational cost.
Keywords: Hybrid simulations; Martini force-field; Mixed models; Multi-scale simulations

Dynamic structure of the lipid bilayer and its modulation by small molecules - Sengupta, Durba; Huster, Daniel (Journal of Physical Chemistry B, 2025)

Is GCR1 the GPR157 of plants? - Gotkhindikar, Aditi; Chakravorty, David; Sengupta, Durba; Joshi, Manali; Assmann, Sarah M. (PLANT PHYSIOLOGY, 2025)

Membrane remodeling by the caveolin-1 8s oligomeric complex - Malshikare, Hrushikesh; Sengupta, Durba (Biophysical Journal, 2025)
Caveolin-1 is a scaffolding protein crucial for the formation of caveolae, specialized membrane structures that are involved in diverse cellular processes such as endocytosis, mechanosensing, and lipid regulation. Recently, a unique structure of the 8S oligomeric complex of caveolin-1 was resolved by cryoelectron microscopy, providing a foundational basis for understanding its molecular mechanisms. In this study, we probe the membrane interactions of the oligomeric caveolin-1 complex in membrane lipid bilayers and vesicles. We performed coarse-grained molecular dynamics simulations to delineate the interactions of the palmitoylated and nonpalmitoylated caveolin-1 with multicomponent membranes. During the simulations, the caveolin-1 complex binds to the membranes, partially to one of the leaflets in a shallow monotopic arrangement. A remodeling of the lipids in its vicinity of the complex was observed in both vesicles and planar bilayers. However, the caveolin-1 complex binds to vesicles without inducing any significant change to the curvature, whereas it appears to induce increased curvature in the planar bilayers leading to the formation of highly curved nanodomains. Cholesterol and phosphoserine lipid enrichment, hallmarks of caveolin-1 binding, were observed in a membrane topology-dependent manner. The differential cholesterol clustering observed between vesicles and bilayers highlights the curvature-dependent nature of caveolin-1-mediated lipid organization. Our work highlights the dual significance of lipid organization and membrane topology in the functional dynamics of caveolin-1, shedding light on its role in inducing and sensing membrane curvature, which is pivotal for various cellular processes. SIGNIFICANCE The rather unanticipated experimental structure of the oligomeric complex of caveolin-1 has opened up multiple questions such as how caveolin-1 interacts with cell membranes and how curvature can be induced or stabilized by a relatively flat protein complex. Here, we identify the molecular mechanisms underlying membrane curvature by caveolin-1 using coarse-grained molecular dynamics simulations. We show that the caveolin-1 complex can bind in a shallow monotopic arrangement and initiate clustering cholesterol and phosphoserine lipids. In vesicles, caveolin-1 binding does not lead to differences in curvature, but binding to planar bilayer leads to the formation of highly curved nanodomains. Our work is an important step to identify novel mechanisms of caveolin-1 stabilized or induced membrane curvature.

Molecular interactions of the pioneer transcription factor GATA3 With DNA - Gharui, Sowmomita; Sengupta, Durba (Proteins-Structure Function and Bioinformatics, 2025)
The GATA3 transcription factor is a pioneer transcription factor that is critical in the development, proliferation, and maintenance of several immune cell types. Identifying the detailed conformational dynamics and interactions of this transcription factor, as well as its clinically important population variants will allow us to unravel its mode of action. In this study, we analyze the molecular interactions of the GATA3 transcription factor bound to dsDNA as well as three clinically important population variants by atomistic molecular dynamics simulations. We identify the effect of the variants on the DNA conformational dynamics and delineate the differences compared to the wildtype transcription factor that could be related to impaired function. We highlight the structural plasticity in the binding of the GATA3 transcription factor and identify important DNA-protein contacts. Although the DNA-protein contacts are persistent and appear to be stable, they exhibit nanosecond timescale fluctuations and several binding/unbinding events. Further, we identify differential DNA binding in the three variants and show that the N-terminal binding is reduced in two of the variants. Our results indicate that reduced minor groove width and DNA diameter are important hallmarks for the binding of GATA3. Our work is an important step towards understanding the functional dynamics of the GATA3 protein and its clinically significant population variants.
Keywords: DNA-protein interactions; GATA protein; Molecular dynamics simulations; molecular mechanism; population variants; transcription factor

A Molecular View of Lipid Nanoparticles: Insights into their Morphology and Structural Plasticity - Porte, Sudha; Vadhana, V.; Sengupta, Durba (Small, 2025)
Lipid nanoparticles (LNPs) have emerged as versatile delivery vehicles for nucleic acid-based therapeutics. Despite their increasing importance, the molecular structure and physico-chemical characteristics of LNPs still remain unclear. In this review, the structural features and phase behavior of LNPs are highlighted. First, the various compositional elements, such as cationic lipids, helper lipids and sterols are discussed, illustrating their functional roles in the self-assembly and stability of LNPs. Molecular models derived from experimental and computational approaches are discussed to provide insights into the structural organization of the LNP components. The influence of sterols and helper lipids in modulating LNP architectures, including membrane fluidity and phase separation, which are key factors for both fusion potential and endosomal escape, is discussed. Variations in sterol content and headgroup chemistry can induce transitions from lamellar to non-lamellar structures, thereby influencing gene transfection outcomes. Further, how cationic lipids induce structural phase transitions, such as lamellar-to-hexagonal and inverse cubic rearrangements under physiological and acidic pH, mimicking extracellular and endosomal conditions, are described. These transitions play a pivotal role in ribonucleic acid (RNA) release and membrane fusion events. This comprehensive review allows to reconcile molecular and structural dynamics that would be necessary for rational design of RNA delivery systems.
Keywords: drug delivery; lipid nanoparticles; phase separation; vaccine delivery

Underutilization of India’s trained science and technology workforce: Impact on gender disparity - Jugran, Arun K.; Sardana, Neha; Fatima, N. Nishad; Maheshwary, Sugandha; Sengupta, Durba; Chakravorty, Nishant (Proceedings of the Indian National Science Academy, 2025)
The growing STEM workforce of India faces remarkable underutilization, mostly among women and early-career researchers. A survey was conducted among 106 research professionals showed that 46% of the respondents experienced career breaks while only 20–22% perceived sufficient employment opportunities across educational levels. Gender disparity has become a remarkable, associated factor, influenced by and perpetuating the underutilization of the workforce, shaped by career interruptions associated to marriage, childbirth, and societal norms, which disproportionately affect 65% of women respondents. While over 50% respondents showed their interest in developing entrepreneurship, awareness of government schemes such as Startup India and Skill India remains inadequate. The findings from the study supports the short-term actions like childcare support and flexible re-entry policies, medium-term incorporation of entrepreneurship programs with scientific careers, and long-term development of R&D through increased investment and mentorship programs. Addressing systemic and gender-based obstacles is vital for optimizing scientific workforce and promoting development driven by innovation in India. Additionally, the promotion of scientific entrepreneurship and start-up schemes is essential for boosting research sector growth. Addressing the systemic barriers and supporting gender equity in science and academia can help India fully leverage its qualified STEM talent.

Increased cholesterol interactions in the active conformational state of the glucagon-like peptide-1 receptor - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2026)
The glucagon-like peptide-1 receptor (GLP-1R) is a class B G-protein-coupled receptor that plays an important role in metabolic regulation and consequently is a target for type 2 diabetes and obesity therapeutics. Although cholesterol has been reported to be implicated in receptor activation, its interactions with the receptor during the activation cycle have not been probed. Using coarse-grained molecular dynamics simulations, we have characterized the cholesterol interactions with GLP-1R in four conformational states: the inactive, partially active, GLP-1-bound active, and exenatide-bound active conformational states. We observed that the cholesterol hotspots vary between the receptor states with an increased enrichment of cholesterol around the receptor in the active conformational states. Importantly, more favorable interaction energetics and increased residence times of cholesterol were identified in the active conformational state of the receptor, although lower in magnitude than previously reported. Notably, subtle differences could be distinguished between the GLP-1-bound and exenatide-bound receptor, underlining the ligand-specific effects. Our findings emphasize the increased selectivity of cholesterol toward the active state of GLP-1R and highlight the role of conformational dynamics in receptor-lipid interplay. Our work helps to understand how cholesterol modulates GLP-1R, with potential effects on its role as a regulator in lipid metabolism, thereby opening avenues to leverage these lipid interactions in targeted drug therapy. SIGNIFICANCE This study provides an understanding of how cholesterol directly influences the function of GLP-1R, a key therapeutic target for metabolic diseases including type 2 diabetes and obesity. Using coarse-grained molecular dynamics simulations, we show that cholesterol binding, favorable interactions, and residence times increase when GLP-1R is in its active states. These interactions vary subtly depending on the activating ligand, highlighting ligand-specific effects. Our findings highlight the critical role of conformational dynamics in receptor-lipid interplay and suggest that understanding these cholesterol-GLP-1R interactions could pave the way for novel strategies in targeted drug therapy for metabolic disorders.

Mechanistic principles of antimicrobial peptides uncovered by charge density-based machine learning - Malshikare, Hrushikesh; Priyakumar, U. Deva; Chatterjee, Prathit; Sengupta, Durba (Chemical Communications, 2026)
Antimicrobial peptides (AMPs) are emerging as potent alternatives to conventional antibiotics, yet their diverse nature due to divergent mechanisms of action hinders rational design. Here, we present an electrostatics-stratified computational framework that uncovers key physicochemical principles governing AMP activity. Experimentally validated peptides were grouped by average charge per residue (i.e., the charge/length of the peptide) and analyzed through integrated sequence-, structure-, and chemistry-based descriptors. Distinct molecular signatures emerged across electrostatic regimes: low-charge/length peptides rely on amphipathic organization via structural compactness, whereas the intermediate-charge/length peptides exhibit balanced hydrophobicity and electrostatics. The high-charge peptides couple strong cationic attraction with lipophilicity and tryptophan anchoring to mainly disrupt membranes. Interestingly, hydrophobic moment, which is a measure of the amphipathicity, is found to be important in all three classes of AMPs. This study identifies distinguishing features of AMP sub-groups and suggests design guidelines for developing selective and potent next-generation AMPs.

Noncanonical regulation of the plasma membrane copper transporter CTRL through modulation of membrane mechanical properties - Chatterjee, Subhendu K.; Kar, Sumanta; Nikte, V, Siddhanta; Dash, Tisha; Ghosh, Tanmoy; Paul, Mrittika; Maji, Saptarshi; Sengupta, Durba; Sinha, Bidisha; Gupta, Arnab (Molecular Biology of the Cell, 2026)
We describe a noncanonical, membrane receptor-like regulation of the human copper transporter-1 (CTR1) in response to copper stimuli. CTR1 is the sole high-affinity trimeric plasma-membrane copper-importing channel that self-regulates by undergoing endocytosis to limit copper uptake. We observed that preceding copper-induced endocytosis, CTR1 forms clusters on the plasma membrane, a phenomenon that is typically observed in membrane receptors. We deciphered the mechanism of CTR1 clustering and studied its ramifications on the physical properties of plasma membranes harboring these clusters that could favor endocytosis. Membrane tension and fluctuation are fundamental regulators of pre-and post-endocytic events. Using coarse-grain molecular dynamics (MD)-simulations and coupled interference reflection microscopy-total internal reflection fluorescence microscopy (TIRF) we demonstrated that CTR1 clusters induce positive membrane curvature, an increase in local membrane tension, and a decrease in local membrane fluctuation; alterations that favor the formation of endocytic pits. Clustering is facilitated by copper sequestering methionine-rich extracellular amino-terminus of CTR1. MD-simulations and IRM-TIRF imaging revealed that CTR1 clustering is facilitated by membrane cholesterol, depletion of which delays CTR1 endocytosis. CTR1 clustering promotes clathrin-coated pit formation that engages recruitment of adaptor protein AP-2. To summarize, we report hitherto unknown ``pre-endocytic'' ``receptor-like'' phenomenon of ligand-induced clustering of a metal channel, which in turn regulates self-endocytosis by modulating membrane properties.

Recognition of diverse GATA motifs necessitates multimodal GATA3-DNA binding - Gharui, Sowmomita; Puntambekar, Shraddha; Sarkar, Ram Rup; Narlikar, Leelavati; Sengupta, Durba (Biochemical and Biophysical Research Communications, 2026)
GATA3 is a pioneer transcription factor that plays a central role in the formation, proliferation, and sustenance of various immune cell types, notably serving as the ``master regulator'' of T helper 2 (Th2) cell differentiation. It regulates gene expression by recognizing the canonical DNA consensus motif (A/T)GATA(A/G) through its highly conserved zinc finger domains. However, beyond this classical binding motif, emerging evidence indicates that GATA3 also recognizes a varied array of noncanonical and palindromic sequence motifs, but the underlying molecular mechanisms are unclear. In this review, we discuss an emerging aspect of GATA3 function that links these diverse DNA sequence motifs to varying structural binding modes and finally to differential chromatin outcomes. We discuss how the alternative sequence motifs may engage the two zinc finger domains differently, leading towards a multitude of binding modes underlying this diverse motif recognition. The spacer length between the GATA motifs has been shown to modulate DNA binding and the geometric constraints imposed may help determine the binding mode. We reanalyzed previous data and show that these diverse motifs, as well as the spacers, modulate nucleosomal outcomes, highlighting the importance of these motifs in GATA3 function. Several disease-associated mutations, such as those implicated in autoimmune diseases and cancer, have been reported for GATA3, and we discuss how these mutations alter the binding of the zinc finger domains. This link between sequence recognition and DNA binding modes represents an underexplored aspect of GATA3 function that is necessary for understanding its multifaceted regulatory role in human health and disease.
Keywords: GATA; Mutations; Nucleosome; Palindrome; Reverse palindrome; Spacers; Tandem

Specificity and promiscuity of phosphoinositide lipid interactions with the serotonin1A receptor: insights from submillisecond coarse-grain simulations - Nikte, Siddhanta V.; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2026)
G protein-coupled receptors (GPCRs) are lipid-dependent membrane receptors that serve as important cell signaling hubs. Phosphoinositide (PIP) lipids represent an important class of anionic lipids that play vital roles in neuronal function and signaling. PIP lipids have been reported to modulate GPCR function, although the specificity and molecular details of the interactions are still not clear. An important GPCR in this context is the serotonin(1A) receptor, a neurotransmitter GPCR, which has been reported to interact with phosphatidylinositol 4-phosphate (PIP1) lipids. In this work, we computationally analyzed the specificity of the serotonin(1A) receptor-PIP lipid interactions using coarse-grain molecular dynamics simulations. Our results predict that four anionic lipid sites are present at the receptor surface, although the relative populations are dependent on the lipid type. PIP1 lipids exhibit the highest interaction at a charged cleft formed by transmembrane helices VI and VII. We observed electrostatic interactions at a cluster of charged residues (Arg341, Lys342, Lys345) and hydrophobic and aromatic interactions at residue Ile349 and Tyr402. In contrast, phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) lipids interact more with transmembrane helix IV. We observed that anionic phospholipids such as phosphatidylserine (PS) interact at these sites, although their occupancy at these sites is much reduced. By elucidating the molecular determinants of these interactions in silico, this study generates novel, testable hypotheses regarding the functional role of specific lipid-receptor contacts. Our work constitutes an important step in analyzing molecular signatures of phosphoinositide lipid-GPCR interactions in the overall context of diverse roles of phosphoinositides in neuronal function and signaling.
Keywords: anionic lipids; Cholesterol; GPCR; MARTINIcoarse-grain simulations; PIP lipids; serotonin(1A) receptor

Unique microswitches positioned extracellular to the orthosteric binding site initiate activation in the β1-adrenergic receptor - Koulgi, Shruti; Harman, Thomas H.; Jones, Andrew J. Y.; Sonavane, Uddhavesh; Nietlispach, Daniel; Sengupta, Durba; Joshi, Manali (Journal of Chemical Information and Modeling, 2026)
Class A GPCRs are known to bind an astonishingly diverse set of agonists, ranging from ions and small molecules to peptides and large proteins that activate these receptors. Interestingly, despite this diversity, agonist binding is described to trigger a conserved activation pathway that propagates changes from beneath the orthosteric agonist-binding site toward the intracellular G protein-coupling site. This suggests the presence of receptor-specific residues upstream of the orthosteric agonist-binding site that not only enable recognition of the ligand but also trigger the common activation mechanism. Using the prototypical beta 1AR-G protein system, we employed microsecond time-scale atomistic molecular dynamics simulations together with NMR experiments to investigate how receptor-specific residues, in conjunction with agonist binding, initiate the conserved activation pathway. We identified state-dependent electrostatic and hydrophobic switches involving unique beta 1AR residues located above the orthosteric binding site, potentially linking them to receptor activation. Our simulations recapitulated the known common activation pathway and also uncovered beta 1AR-specific novel contacts. Additionally, we identified a unique water-mediated R-Y-Y switch near the intracellular end that could facilitate G protein coupling. Overall, based on our work, we propose how evolutionary variations in the extended ligand-binding site could enable receptor-specific agonist recognition, triggering and converging on the common activation mechanism and preserving G protein coupling fidelity.